2018
DOI: 10.1016/j.ces.2018.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Silanol-rich platelet silica modified with branched amine for efficient CO2 capture

Abstract: In this work, we report a new route to improve the CO 2 adsorption performance of solid amine adsorbents. Platelet mesoporous silicas with abundant surface silanols were prepared by emulsion synthesis followed by simple solvent extraction. These silanol-rich silica particles were then functionalized with branched polyethyleneimine (BPEI) by grafting or impregnation to prepare CO 2 adsorbents. Silanol-rich silicas grafted with BPEI exhibited 70% higher amine density and 47% higher CO 2 adsorption capacity than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 32 publications
2
7
0
Order By: Relevance
“…Overall, our results seem to show that iodine adsorption takes place mostly in the mesopores for low-medium PEI contents and outside of the porosity or at the pore mouth when the pores are getting totally filled with PEI. Consistently with our results, literature studies also indicate optimum organic loadings in the range 30-50 wt% in the case of CO2 adsorption by PEI-silica materials [24,[32][33][34]. At higher PEI contents, the diffusion of CO2 was found to be severely hindered by the high concentration of PEI molecules in the porosity.…”
Section: Chemical and Thermal Analysessupporting
confidence: 91%
“…Overall, our results seem to show that iodine adsorption takes place mostly in the mesopores for low-medium PEI contents and outside of the porosity or at the pore mouth when the pores are getting totally filled with PEI. Consistently with our results, literature studies also indicate optimum organic loadings in the range 30-50 wt% in the case of CO2 adsorption by PEI-silica materials [24,[32][33][34]. At higher PEI contents, the diffusion of CO2 was found to be severely hindered by the high concentration of PEI molecules in the porosity.…”
Section: Chemical and Thermal Analysessupporting
confidence: 91%
“…[1][2][3] Solid amine adsorption technology, with weak corrosivity, highly efficient adsorption performance and low regeneration energy consumption, is recognized as an effective method. [4][5][6][7] So far the study of amine-loaded solid sorbents mainly focuses on immobilizing amines onto the inner surface of porous supporting materials, such as metal-organic frameworks (MOFs), [8][9][10][11][12][13] mesoporous molecular sieves, 14-22 silicas [23][24][25][26][27][28][29][30][31] and so on. [32][33][34][35][36][37][38][39][40] Chen et al incorporated polyethyleneimine (PEI) into mesoporous zeolite 13X prepared by pore-expanding original micropores; due to PEI-dispersion in mesopores, the CO 2 adsorption capacity for PEI-modied 13X reached 80 mg g À1 at 100 C under a pure CO 2 atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…However, most studies focused on tailoring of the pore structure are aiming to mainly modifying the pore size and pore volume of cylindrical pores: Therefore, the design of pore shape to further modify the loading of organic amines in pores, which is also important for releasing free pore space along with the modifying of pore properties, should also be considered and remains to be explored. Moreover, a few studies reported that the changes of amine assembly can also significantly influence the sorption performance [26,27]; however, the design and fabrication of sorbents with arranged amine assembly are still challenging. More importantly, the influence of nano pore structure and amine assembly on sorption and desorption kinetics, which is of great importance for the future design of sorbents, is also unclear.…”
Section: Introductionmentioning
confidence: 99%